Risk-oriented strategic management accounting in Ukraine - Fomina, Olena; Semenova, Svitlana; Moshkovska, Olena; Yevdoshchak, Volodymyr; Manachynska, Yulia (Business: Theory and Practice, 2023)
In order to survive, Ukrainian enterprises in the conditions of war must look for new ways of effective management, a higher degree of integration of risk management and strategic management. Management accounting helps make risk-based decisions to achieve strategic goals. The expert survey method made it possible to identify the most significant risks for enterprises in Ukraine in war conditions: the risk of increased costs, reduced income, the risk of inability to repay obligations, loss of customers, non-payment of receivables, loss of asset value, risk of unprofitability, reduction of business and bankruptcy. The strategic management accounting risk matrix shows the probability and potential impact of each risk on accounting data. A strategic plan and measurement of the effectiveness of risk-oriented strategic management accounting was developed. It shows the relationship of accounting objects, the financial statements of the enterprise, with analytical indicators for assessing the financial condition and the impact of risks under pessimistic, optimistic and optimal scenarios. In practice, it helps to identify risks, determine their impact on enterprise performance indicators, model indicators, assess their compliance with strategic goals, adapt in a timely manner, and make effective management decisions.